2022
DOI: 10.3390/microorganisms10101922
|View full text |Cite
|
Sign up to set email alerts
|

Co-Fermentations of Kveik with Non-Conventional Yeasts for Targeted Aroma Modulation

Abstract: Kveik are consortia of yeast used for farmhouse ale production in Western Norway. Yeast strains derived from these mixtures are known, for example, for their high fermentation rate, thermotolerance, lack of phenolic off flavor production (POF-) and strong flocculation phenotype. In this study, we used five single cell yeast isolates from different Kveik yeasts, analyzed their fermentation and flavor production, and compared it with a typical yeast used in distilleries using 20 °C and 28 °C as the fermentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…In addition to the direct applied value of landrace brewing strains, they are also valuable from a strain development perspective. Compared to ‘Beer 1’ strains, which tend to be sterile (Gallone et al 2016; De Chiara et al 2022), the majority of the kveik strains that have been tested so far have been fertile (Preiss et al 2018; Dippel et al 2022). This means that kveik strains can be quite readily used for breeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the direct applied value of landrace brewing strains, they are also valuable from a strain development perspective. Compared to ‘Beer 1’ strains, which tend to be sterile (Gallone et al 2016; De Chiara et al 2022), the majority of the kveik strains that have been tested so far have been fertile (Preiss et al 2018; Dippel et al 2022). This means that kveik strains can be quite readily used for breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Limited work has so far been carried out on the phenotypic diversity of farmhouse yeasts. Prior work on a relatively small subset of ‘kveik’ isolates has revealed that they tend to ferment wort rapidly, have high thermotolerance, and can produce beers ranging from clean and neutral to strongly aromatic (Preiss et al 2018; Foster et al 2022; Kawa-Rygielska et al 2022; Habschied et al 2022; Dippel et al 2022). Here, we reveal that farmhouse yeast, including kveik, show significant phenotypic diversity, both in regards to fermentation dynamics and flavour formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kveik yeast, traditional Norwegian farmhouse yeast, has gained attention in brewing due to its phenolic off-flavour negativity, high fermentation rate, tolerance to high temperatures (>28°C), and classification within the S. cerevisiae clade (Preiss et al 2018 ). This interest has extended to the distilling industry, where Kveik yeast demonstrates a fermentation pattern similar to commercial distilling yeast and a distinct flavour profile, offering the opportunity for development of new products (Dippel et al 2022 , Horstmann et al 2023 ).…”
Section: Non-conventional Yeast Used For Distilled Spiritsmentioning
confidence: 99%
“…Apesar da levedura kveik apresentar em geral maior tolerância ao álcool comparado com outras leveduras cervejeiras como a Saccharomyces cerevisiae, algumas cepas não são capazes de fermentar maltotriose e isso pode explicar o resultado do baixo teor de álcool da kveik neste estudo, pois a maltotriose é um açúcar que a S. cerevisiae utilizada consegue metabolizar. (DIPPEL et al, 2022) CONCLUSÃO Neste estudo, foi feita a comparação das duas leveduras, Kveik e Saccharomyces cerevisiae. Foi possível observar que, com as mesmas condições de temperatura e com o mesmo mosto, as leveduras apresentaram fermentações com velocidades diferentes, porém chegaram a resultados de densidade e pH muito próximos e na análise de teor alcoólico foi de aproximadamente 1,17% de diferença uma da outra, tendo a S. cerevisiae produzido mais.…”
Section: Fonte: Própriaunclassified